The Influence of Search, Solve, Create, and Share (SSCS) Learning Models on Critical Thinking Ability and Learning Outcomes of Padamata Students Learning Class V SDN 12 Palu - Yanti, Yanti; Hatibe, Amiruddin; Rede, Amran (Jurnal Riset Pendidikan MIPA, 2019)
The purpose of this research is to know the effect of the search, solve, create, and share (SSCS) learning model on critical thinking ability and student learning outcomes in science subjects. The sampling technique is purposive sample population through the experimental method, this research population is the students of class V SDN 12 Palu. Based on the result of data analysis, it can be concluded that: 1) there was the influence of learning model search, solve, create and share (SSCS) to student critical thinking ability on science subjects with human and animal organ material; 2) there was the influence of learning model of search, solve, create and share to student learning outcomes on science subjects with human and animal organ material: 3) the average gain after the posttest in the experimental class was 82.97; 4) the results of observation of teacher activity and observation of student activities can be said to be good.